Les représentations et la place de la littérature française/francophone dans les pratiques de lecture des étudiants des universités européennes - Krawczyk, Dariusz; Obszyński, Michał; Smuk, Maciej (2023)
The aim of this article is to present the results of research carried out within the European perspective on Literature, Culture, Language and Certification (EpoLCLC) project, according to three main axes: contemporary reading practices and the image of French literature among contemporary readers in a sociological approach; reading strategies of foreign language texts in a psycholinguistic approach; the place of translations and the representation of the role of the literary translator among contemporary readers in the light of conceptions related to cultural transfers and the global circulation of literature. The analysis and interpretation of the data collected during the course of the project will make it possible to compare the image we have of literature and the reader in our time with a set of real practices and beliefs, as defined by the people questioned during the study. More generally, it will be a question of drawing up, again from the data collected, a portrait of the European student as a reader and of defining the place that French and Francophone literature occupies in his or her daily practices.
Keywords: Francophone literature; reading practices; teaching French as a foreign language; representations; literary translation; cultural transfers; European universities